Automatic Tomatoes Plant Watering System using Internet of Things - Muhammad Adhib Eriansyah; Hambali Hambali (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Tomatoes plant is one of a plant that has a promised business opportunity, especially in Indonesia. The quality and output from tomatoes plant can be improved by paying attention to soil moisture and temperature of the plant, those things can be recked by watering the plant. Normally people do plant watering manually, that way was less effective because of water debit was not match to its need. Therefore smart automatic watering tomatoes plant and monitoring using internet will be needed, so quality and output can be improved, also farmer duty can be a lot easier. This device consists of DHT22 and soil moisture sensor as measures indicator of plant temperature and soil moisture, NodeMCU as connector between arduino and internet, 12V DC pump for watering tool, relay as contact for controlling the pump, and arduino as the main system to run the watering that going starts when the moisture level below 60% and stop at 75%. Arduino is used to receive data from sensors and send it to nodeMCU that connected to the internet, so user can monitor tomatoes plant via internet.